Spiral-staircase photonic structures of metallic nanorods - A. Christofi; N. Stefanou; G. Gantzounis; N. Papanikolaou (Physical Review B, 2011)
By employing the layer-multiple-scattering method, properly extended to periodic assemblies of arbitrarily oriented axis-symmetric particles, we investigate the optical response of a three-dimensional spiral-staircase structure of metallic nanorods. We show that the combination of plasmonic modes and helical arrangement of the nanorods results in the formation of collective optical eigenmodes with a specific predominant circular polarization character, sizable polarization gaps, and negative group velocity bands that lead to negative refraction. Moreover, we demonstrate that multilayer slabs of the given crystal exhibit strong optical activity and circular dichroism combined with reduced dissipative losses, which make the proposed structure potentially useful for polarization control applications in miniaturized optoelectronic devices.